The microbiome and lung cancer: microbial effects on host immune responses and treatment outcomes - Bailey, Alexis; Leuther, Kerstin K.; Robinson, Lary A. (Frontiers in Microbiomes, 2025)
The human microbiome plays a critical role in shaping physiological processes, immune system function, metabolism, and disease development. Recent research has highlighted the microbiome’s profound cancer impact, particularly on lung cancer. This review explores how microbial communities in lung and gut influence tumor progression, immune responses, and treatment outcomes as well as describing the interactions between the microbiome and the host immune system in modulating the efficacy of cancer therapies. Emerging evidence from preclinical and clinical studies investigating the role of the lung and gut microbiome in lung cancer focus on alterations in the microbiota that influence the tumor microenvironment, modulate immune responses, and potentially enhance/hinder treatment effectiveness such as chemotherapy, targeted therapies, and immunotherapy. Microbial diversity plays a significant role in immune regulation, and specific microbial species may activate/suppress immune cells such as T-cells, dendritic cells, and macrophages. Furthermore, this review examines the therapeutic implications of microbiome modulation, including the use of probiotics, antibiotics, and fecal microbiota transplantation in enhancing cancer therapies. Alterations in the lung and gut microbiome and their interaction in the recently described gut-lung axis with its bidirectional communication significantly influence the tumor microenvironment and systemic immune responses. These findings suggest that microbial diversity can regulate immune functions, with specific species capable of activating or suppressing immune cell activity. Furthermore, microbiome-targeted interventions show potential in improving the effectiveness of treatments including chemotherapy, targeted therapies, and immunotherapy, underscoring the importance of the microbiome as a key factor in lung cancer pathogenesis and treatment.